2017
DOI: 10.1002/ece3.3108
|View full text |Cite
|
Sign up to set email alerts
|

Life history constraints explain negative relationship between fish productivity and dissolved organic carbon in lakes

Abstract: Resource availability constrains the life history strategies available to organisms and may thereby limit population growth rates and productivity. We used this conceptual framework to explore the mechanisms driving recently reported negative relationships between fish productivity and dissolved organic carbon (DOC) concentrations in lakes. We studied populations of bluegill (Lepomis macrochirus) in a set of lakes with DOC concentrations ranging from 3 to 24 mg/L; previous work has demonstrated that primary an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 61 publications
(100 reference statements)
0
18
0
Order By: Relevance
“…Karlsson et al () noted a decrease in fish biomass with increasing lake DOC concentration, which they equated with an increase in lake color. Similarly, Craig et al () recently reported that bluegill from humic lakes were smaller in body size and had reduced fecundity compared to those in clear lakes. Taipale et al () noted that perch from lakes with high phosphorus and dissolved organic carbon concentrations generally had smaller body sizes, which correlated with lower concentrations of nutritional EPA and DHA fatty acids.…”
Section: Discussionmentioning
confidence: 82%
“…Karlsson et al () noted a decrease in fish biomass with increasing lake DOC concentration, which they equated with an increase in lake color. Similarly, Craig et al () recently reported that bluegill from humic lakes were smaller in body size and had reduced fecundity compared to those in clear lakes. Taipale et al () noted that perch from lakes with high phosphorus and dissolved organic carbon concentrations generally had smaller body sizes, which correlated with lower concentrations of nutritional EPA and DHA fatty acids.…”
Section: Discussionmentioning
confidence: 82%
“…The role of allochthonous inputs of DOM as the trophic basis of lake productivity remains contested, and our review has pointed to some conflicting literature findings. Survey results indicate that browning tends to reduce productivity at primary and higher trophic levels (e.g., Craig, Jones, Weidel, & Solomon, ; Kelly et al., ), but recent experimental manipulations of DOM inputs (albeit a smaller concentration increase than the surveys encompassed) showed a positive impact on both phytoplankton and zooplankton productivity (Kelly et al., ; Zwart et al., ). Conflicting results highlight the need for more experimental studies, improved understanding of the link between DOM and changes in light and nutrient availability, and documentation of contexts that may condition the response to DOM inputs.…”
Section: Research Prioritiesmentioning
confidence: 99%
“…For example, DOC affects light attenuation, oxygen and nutrient availability, and consequently the development of thermal stratification and hypoxia as well as species distributions and habitat availability 4,5 . Examples of chemical and biological repercussions of the current browning trend include reduced fish growth 6,7 , more favourable conditions for toxin-producing cyanobacteria blooms 8 , reduced potential for the inactivation of pathogens by solar ultraviolet radiation 9 , and increased contaminant transport 10,11 .…”
Section: Introductionmentioning
confidence: 99%